Increasing children’s physical activity through a teaching-assistant led extracurricular intervention: process evaluation of the action 3:30 randomised feasibility trial - Jago, Russell; Sebire, Simon; Davies, Ben; Wood, Lesley; Banfield, Kathryn; Edwards, Mark J.; Powell, Jane E.; Montgomery, Alan A.; Thompson, Janice; Fox, Kenneth (BioMed Central, 2015)
Background Many children do not engage in recommended levels of physical activity (PA), highlighting the need to find ways to increase children’s PA. Process evaluations play an important role in improving the science of randomised controlled trials. We recently reported the results of the Action 3:30 cluster randomised feasibility trial illustrating higher levels of moderate to vigorous intensity PA among boys but not girls. The aim of this paper is to report the process evaluation results including intervention fidelity, implementation, context and how intervention components and trial design could be improved before proceeding to a definitive RCT.